The use of immersive virtual reality for managing physical and psychological distress in children and adolescents with cancer undergoing chemotherapy via implanted vascular access device needle insertion: A systematic review - Tsitsi, Theologia; Michail, Koralia; Christou, Frederick G.; Charalambous, Andreas (My University, 2024)
Children and adolescents undergoing cancer treatment often endure distressing procedures, leading to pain and anxiety. Immersive virtual reality (VR) is a novel distraction technique for distress management, but research in pediatric oncology remains limited. This systematic review aims to assess the effectiveness of IVR intervention utilizing advanced head-mounted displays, in alleviating physical and psychological distress among Children and Adolescents diagnosed with malignancies undergoing chemotherapy treatment via Implantable Venous Access Device/Port (IVAD/P) (P) needle insertion. Additionally, the study evaluates the usability and acceptability of the IVR intervention among healthcare professionals, patients, and their parents.
Keywords: cancer; children; AYA; Virtual reality